The changing roles of the state and transnational corporations in the development of mining in Zambia : an evaluation of influences on the transition from state to private ownership of the mining sector - Ahmed, Rahima (My University, 2011)
This dissertation principally analyses: (i) the privatisation of Zambia’s copper mines; (ii) the impact of state and private ownership and control of the mines on development; and (iii) the roles of mining TNCs in the Zambian economy. The research covers the period from independence in 1964 to 2006/7, but mainly focuses on the 1991 to 2006/7 period. The validity of several neo-classical theoretical views and counter-arguments pertaining to the social and economic benefits of privatisation and the private ownership and the activities of mining TNCs is tested in the mining sector study. The methodology is based on a case study comprising fieldwork and literature research, utilising a qualitative approach and an inductive method. The conclusions of the study could enhance knowledge from which other developing countries intent on privatising their SOEs could draw, as privatisation studies of sub-Saharan countries have mostly overlooked analyses of the social impact of the private ownership of enterprises. Key findings of the study are that the privatisation and private ownership of the mines by TNCs have failed to produce net positive socio-economic outcomes for Zambia. Furthermore, under private ownership of the mines, the political-economic benefits have shifted, mainly concentrating the surpluses from mining in favour of mining TNCs. The primary recommendations from the study are that certain measures, in particular a strong state capacity, are fundamental in enabling greater and more equitable redistribution of benefits for the country from privatisation, private ownership and the economic activities of mining TNCs.
Keywords: Zambia; Mining; Privatisation; Private ownership; State ownership